2019
DOI: 10.3389/fimmu.2019.02357
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cells in Myeloid Malignancies: Immune Surveillance, NK Cell Dysfunction, and Pharmacological Opportunities to Bolster the Endogenous NK Cells

Abstract: Natural killer (NK) cells are large granular lymphocytes involved in our defense against certain virus-infected and malignant cells. In contrast to T cells, NK cells elicit rapid anti-tumor responses based on signals from activating and inhibitory cell surface receptors. They also lyse target cells via antibody-dependent cellular cytotoxicity, a critical mode of action of several therapeutic antibodies used to treat cancer. A body of evidence shows that NK cells can exhibit potent anti-tumor activity against c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
106
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(107 citation statements)
references
References 212 publications
(242 reference statements)
1
106
0
Order By: Relevance
“…NK cells preferentially kill cancer stem cells (4,51), including BM-repopulating TKI-resistant BCR-ABL1 + qLSCs (Fig. 5B), and NK-cell quantitative and functional impairment is a feature of patients with untreated and TKI-treated CML (6,52). Impaired NK-cell immunity also associates with CML qLSC persistance in patients with TKI-treated CML in deep molecular remission (28,31), whereas normal levels of activated NK cells characterize patients in sustained treatment-free remission (28) and account for increased disease-free survival after T-cell-depleted stem cell transplant (4), suggesting that NK-cell-based therapies may lead to qLSC eradication.…”
Section: Mir300 Role In Nk Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…NK cells preferentially kill cancer stem cells (4,51), including BM-repopulating TKI-resistant BCR-ABL1 + qLSCs (Fig. 5B), and NK-cell quantitative and functional impairment is a feature of patients with untreated and TKI-treated CML (6,52). Impaired NK-cell immunity also associates with CML qLSC persistance in patients with TKI-treated CML in deep molecular remission (28,31), whereas normal levels of activated NK cells characterize patients in sustained treatment-free remission (28) and account for increased disease-free survival after T-cell-depleted stem cell transplant (4), suggesting that NK-cell-based therapies may lead to qLSC eradication.…”
Section: Mir300 Role In Nk Cellsmentioning
confidence: 99%
“…In fact, persistence of CML-initiating quiescent leukemic stem cells (qLSC) likely depends on their innate and acquired TKI resistance (3) and on impaired natural killer (NK) cell cytotoxicity against leukemic stem cells (LSC) (4), and accounts for disease relapse and dismal outcome (1,5). Clinical trials, aimed at targeting intrinsic mechanisms of TKI resistance, failed to eradicate the TKI-resistant qLSC reservoir, likely because of bone marrow (BM) microenvironment (BMM) protective and inhibitory effects on LSCs and NK cells, respectively (5,6). and -resistant CP and BC phase CML qLSCs and progenitors with neither adverse effects on normal hematopoiesis nor organ toxicity (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TKI therapy not only has a direct effect on onco-protein kinases but also has a key role in restoration of effector cells-mediated immune response such as NK cells, cytotoxic T lymphocytes (CTL) -CD8 and DCs (Figure 2). In vitro and in vivo studies revealed that TKI show the direct and indirect immunomodulatory effects involving natural killer (NK) cells, in particular in patients treated for CML or for GIST tumors [137][138][139]. On the other hand, the use of JAK inhibitors such as ruxolitinib showed a general dampening of immune response, also on NK cells, both in vitro and in vivo, offering an explanation of increase infections rate and of long term sides effects [140,141].…”
Section: Tki-targeted Therapy Effects On Nk Cells In Hematological Mamentioning
confidence: 99%
“…Chretien et al [ 14 ] described three NK cell maturation stages in AML patients (hypermaturation, intermediate maturation and hypomaturation); NK cells with hypomaturation features are associated with a poor prognosis. IMiDs downregulate the expression of HLA class I molecules on AML cells, increase their disruption by NK cells and raise the expression of crucial ligands (particularly ligands of DNAM-1 and NKG2D) involved in blasts recognition [ 12 , 15 ]. Furthermore, these drugs promote NK cell phenotypic modifications, improving the immunological synapse between NK and leukemic cells (upregulation of CD56 and downregulation of KIR2D, NKp30, NKp46 on NK cells) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%